Breadline Britain : the rise of mass poverty - Lansley, Stewart; Mack, Joanna (Television producer) (London : Oneworld, 2015)
"Poverty in Britain is at post-war highs and - even with economic growth - is set to increase yet further. Food bank queues are growing, levels of severe deprivation have been rising, and increasing numbers of children are left with their most basic needs unmet. Based on exclusive access to the largest ever survey of poverty in the UK, and its predecessor surveys in the 1980s and 1990s, Stewart Lansley and Joanna Mack track changes in deprivation and paint a devastating picture of the reality of poverty today and its causes. Shattering the myth that poverty is the fault of the poor and a generous benefit system, they show that the blame lies with the massive social and economic upheaval that has shifted power from the workforce to corporations and swelled the ranks of the working poor, a group increasingly at the mercy of low-pay, zero-hour contracts and downward social mobility. The high levels of poverty in the UK are not ordained but can be traced directly to the political choices taken by successive governments. Lansley and Mack outline an alternative economic and social strategy that is both perfectly feasible and urgently necessary if we are to reverse the course of the last three decades. " -- from publisher's website.
Includes bibliographical references and index.
Keywords: Poor -- Great Britain; Poverty -- Great Britain; Great Britain -- Economic conditions -- 1997-